AN OPTIMUM MODEL OF FISH AUCTION IN INDONESIAN FISHING PORTS IN ACCORDANCE WITH THE CHARACTERISTICS OF FISHERMAN - Ernani Lubis; Anwar Bey Pane (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Fishing Port as the economic center of fisheries is an important component  in  fishing catch system  that  needs to be organized and managed, especially for fish marketing activities.  Indonesian fisherman income which is still low, due to the fish marketing system in the fishing port is unfavorable for the fisherman. The purpose of this study is to formulate an optimum model of the fish auction in the fishing port in order to increase the income of fisherman. Aspects which were studied comprises the major aspects such as the management aspects, socio-economic of fishing and fishing port and following by additional aspects of biotechnic of fishimg port.  It has been obtained the optimum model of the fish auction that is Integrated Model and Modern Fish Auction Model. The model has 2 (two) submodel. Submodel-1 : Integrated Fish auction that is a gradually and directionally implementation model of fish auction in the Fish Landing Base with due respect to the readiness of the auction and the integration courtier/skipper’s (punggawa) role. This model also consider the readiness to the auction minimum and effective standards to ensure the quality of fish and sanitation in fish auction place and rearrangement the role of courtier/skipper. This model can be applied to Pontap Fish Landing Base.  Submodel-2 : Modern and Continuous Fish Auction Model, that is a gradually and directionally implementation model of the fish auction with due respect to improving modernization of actual fish auction standards. This model can be applied to Palabuhanratu Territorial Fishing Port.